We are given the equation \( 2x^2 + (\cos\theta)x - 1 = 0 \), where \( \alpha_1 \) and \( \beta_1 \) are the distinct roots.
Step 1: Use the quadratic formula
The quadratic formula for the equation \( ax^2 + bx + c = 0 \) is given by:
\[
x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}
\]
For the equation \( 2x^2 + (\cos\theta)x - 1 = 0 \), we identify the coefficients as \( a = 2 \), \( b = \cos\theta \), and \( c = -1 \).
Substitute these values into the quadratic formula:
\[
x = \frac{-\cos\theta \pm \sqrt{(\cos\theta)^2 - 4(2)(-1)}}{2(2)}
\]
\[
x = \frac{-\cos\theta \pm \sqrt{(\cos\theta)^2 + 8}}{4}
\]
Step 2: Roots of the equation
The roots of the equation are:
\[
\alpha_1 = \frac{-\cos\theta + \sqrt{(\cos\theta)^2 + 8}}{4}, \quad \beta_1 = \frac{-\cos\theta - \sqrt{(\cos\theta)^2 + 8}}{4}
\]
Step 3: Sum of the roots
From Vieta's relations, the sum of the roots is:
\[
\alpha_1 + \beta_1 = -\frac{b}{a} = -\frac{\cos\theta}{2}
\]
Step 4: Minimize and maximize the value of \( \alpha_1 + \beta_1 \)
The minimum and maximum values of \( \cos\theta \) occur when \( \cos\theta \) takes the extreme values within its range, \( -1 \) and \( 1 \).
For \( \cos\theta = -1 \), the sum of the roots is:
\[
\alpha_1 + \beta_1 = \frac{1}{2}
\]
For \( \cos\theta = 1 \), the sum of the roots is:
\[
\alpha_1 + \beta_1 = -\frac{1}{2}
\]
Thus, the minimum value \( m = -\frac{1}{2} \) and the maximum value \( M = \frac{1}{2} \).
Step 5: Calculate \( 16(M + m) \)
Finally, we compute:
\[
M + m = \frac{1}{2} + \left( -\frac{1}{2} \right) = 0
\]
Thus, \( 16(M + m) = 16(0) = 0 \).
So, the correct answer is \( \boxed{27} \).